Sexting among high school students in a metropolis in Ghana: an exploratory and descriptive study. Issue 3 (2nd July 2020) - Baiden, F.; Amankwah, J.; Owusu, A.
ABSTRACT: The sharing of sexually explicit materials using internet-enabled devices by adolescents (sexting) is an issue of global concern. Very little is known about it in sub-Saharan Africa. We conducted a self-administered survey among a randomly selected group of high school students in Tema, Ghana. Students' self-esteem was assessed using the Rosenberg Self-Esteem Scale. Analysis including logistic regression explored prevalence and determinants of sexting, as well as its effect on sexual behavior. Five hundred and seventy-six (53% females) students participated. About 24.7% had shared sext materials using mobile phones. The predictors of sexting were being male (adjusted OR = 6.01, 95% CI 3.49–10.35), being in a "serious" (5.91, 2.77–12.64) or "casual" (2.82, 1.67–4.75) relationship and owning a mobile phone (1.82, 1.10–3.02). Students aged >16years (1.48, 0.94-2-34) and students with low self-esteem (1.24, 0.74–2.05) were more likely to be involved in sexting. Sexters were more likely to be sexually active (3.79, 2.33–6.14). Self-gratification and social pressures were the reasons for sexting. Fear that materials could go viral, religiosity and possible reprimand were the reasons students did not engage in sexting. Sexting among adolescents in this population is high and similar to levels in developed countries. Given the possible adverse short and long-term impact, school-based interventions are needed.